2011
DOI: 10.4018/ijimr.2011010101
|View full text |Cite
|
Sign up to set email alerts
|

Open Loop Force Control of Piezo-Actuated Stick-Slip Drives

Abstract: In this paper a new method to generate forces with stick-slip micro drives is described. The forces are generated if the runner of the stick-slip drive operates against an obstacle. It is shown that the generated force can be varied selectively without additional sensors and that virtually any force between zero and a limiting force given by certain parameters can be generated. For the investigated micro actuator this force is typically in the range up to hundreds of mN. For this reason, the method has the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…It has been measured using different methods: making the slider move against a spring, the force is either determined from the deformation of the spring [61,74,75], or using a load cell connected to the spring [76,77]. Other authors make the slider move directly against a load cell [67,[78][79][80][81], or the force is exerted to a part connected to a load cell instead of a slider [82]. (Bergander et al [67] (p. 33) and Kang et al [78] (p. 610) only state that they measured the force of the slider "with a precision balance" respectively "using a digital power gauge".…”
Section: Force Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been measured using different methods: making the slider move against a spring, the force is either determined from the deformation of the spring [61,74,75], or using a load cell connected to the spring [76,77]. Other authors make the slider move directly against a load cell [67,[78][79][80][81], or the force is exerted to a part connected to a load cell instead of a slider [82]. (Bergander et al [67] (p. 33) and Kang et al [78] (p. 610) only state that they measured the force of the slider "with a precision balance" respectively "using a digital power gauge".…”
Section: Force Generationmentioning
confidence: 99%
“…Controlled force generation with inertia motors has been investigated by Edeler et al [79,88,89]. These works have shown that in the investigated motor, the generated force-determined using the spring method-depends on a number of parameters, such as slider mass, friction contact, pre-load, and excitation signal.…”
Section: Force Generationmentioning
confidence: 99%
“…The method was firstly introduced by the same author [12]. It was observed, that it is possible to generate defined, arbitrary forces with miniaturized piezo-driven Stick-Slip drives in a testbed.…”
Section: Open-loop Force Controlmentioning
confidence: 99%
“…Fig. 2: a) Sketch of the testbed which was used to investigate the force generation method (adapted from [12]). b) Image of the Z-axis in the mobile nanohandling robot.…”
Section: Measurements and Validationmentioning
confidence: 99%
“…At present, trans-scale precision positioning technology is divided into four types of driving methods. They are macro-micro hybrid driving (Gloess, 2006), piezoelectric ultrasonic driving (Holmes, Hocken, & Troumper, 2000), inchworm-type driving (Roh & Kwon, 2004) and slip-stick driving (Bergander, Breguet, Schmitt, & Clavel, 2000;Edeler & Fatikow, 2011). The frontal three driving methods can carry out trans-scale movement and have high resolution, but because of their complicated structures and control, they cannot be applied in many nano-manipulation mechanisms in tight and contained space.…”
Section: Introductionmentioning
confidence: 99%